Comparison of two visual methods for detecting caries among obese and non-obese children. (3rd July 2016) - Ferraz, Eduardo Gomes; Silva, Luciana Rodrigues; Sarmento, Viviane Almeida; de Jesus Campos, Elisângela; de Oliveira, Thaís Feitosa Leitão; Magalhães, Juliana Cunha; Paraguassú, Gardênia Matos; Boa-Sorte, Ney
Abstract: Objective : The study aimed to compare two visual methods for detecting caries among obese and non-obese children in Salvador, Brazil. Materials and methods : A cross-sectional study was conducted from 2011–2012, which evaluated 180 paediatric patients, 6–14 years old, girls and boys, categorized into two groups: obese and non-obese (healthy weight), according to the body mass index. For the evaluation of dental caries, the decayed, missing or filled teeth index (DMFT/dmft) and International Caries Detection and Assessment System II (ICDAS II) visual criteria were used. Results : The mean DMFT value was 0.98 in obese children and 0.57 in the non-obese children, without significant differences between groups ( p  = 0.206). The mean dmft value in the non-obese children (1.66) was higher than in obese children (0.95), with significant differences between groups ( p  = 0.021). According to ICDAS II criteria, there was a higher prevalence of non-cavitated enamel lesions (D1–3) in obese children ( n  = 156,  10.5%) compared to the non-obese children ( n  = 55,  1.9%), with significant differences between the groups ( p  < 0.001). Conclusions : The inclusion of non-cavitated lesions during the caries evaluation represents a challenge in diagnosis, which allows for control of this process before the evolution of these lesions to cavitation.